The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1600-0501.2008.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium allergy in dental implant patients: a clinical study on 1500 consecutive patients

Abstract: Ti allergy can be detected in dental implant patients, even though its estimated prevalence is low (0.6%). A significantly higher risk of positive allergic reaction was found in patients showing post-op allergy compatible response (ACRG), in which cases allergy tests could be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
307
2
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(326 citation statements)
references
References 54 publications
6
307
2
11
Order By: Relevance
“…There are, however, esthetic problems associated with the Ti implants due to its gray coloring. Moreover, since Ti originally having the characteristics of biotolerant which cause ion elution by corrosion in some environments, Ti implants have been reported to trigger allergic reactions [1][2][3] . Recently zirconia has drawn attention as a potential alternative to Ti, as it allows both allergic reactions and esthetic problems to be avoided 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, esthetic problems associated with the Ti implants due to its gray coloring. Moreover, since Ti originally having the characteristics of biotolerant which cause ion elution by corrosion in some environments, Ti implants have been reported to trigger allergic reactions [1][2][3] . Recently zirconia has drawn attention as a potential alternative to Ti, as it allows both allergic reactions and esthetic problems to be avoided 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Les auteurs concluent qu'il faut y penser et la rechercher chez les patients souffrant de symptômes d'allergie après une implantation mais aussi devant un échec implantaire inexpliqué et répété [34].…”
Section: Allergie Au Titaneunclassified
“…Sicilia et al [6] reported that the prevalence of titanium allergy in 1500 dental implant patients was about 0.6%, which may induce implant failure by inhibiting implant integration. Although titanium allergy is uncommon, the appearance of significant complications in particularly sensitive patients cannot be disregarded [7].…”
Section: Introductionmentioning
confidence: 99%